2020
DOI: 10.1101/2020.08.13.20173161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralizing antibodies correlate with protection from SARS-CoV-2 in humans during a fishery vessel outbreak with high attack rate

Abstract: The development of vaccines against SARS-CoV-2 would be greatly facilitated by the identification of immunological correlates of protection in humans. However, to date, studies on protective immunity have only been performed in animal models and correlates of protection have not been established in humans. Here, we describe an outbreak of SARS-CoV-2 on a fishing vessel associated with a high attack rate. Predeparture serological and viral RT-PCR testing along with repeat testing after return to shore was avail… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
284
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(294 citation statements)
references
References 58 publications
8
284
0
2
Order By: Relevance
“…Virus neutralizing antibodies can potentially prevent reinfection with SARS-CoV-2 [ 17–19 ]. Therefore, we further assessed in vitro protective immunity against SARS-CoV-2 in HCW with positive or intermediate results by screening RBD ELISA (n = 76) using the MN assay to confirm infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus neutralizing antibodies can potentially prevent reinfection with SARS-CoV-2 [ 17–19 ]. Therefore, we further assessed in vitro protective immunity against SARS-CoV-2 in HCW with positive or intermediate results by screening RBD ELISA (n = 76) using the MN assay to confirm infection.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, virus neutralizing antibodies can potentially prevent reinfection with SARS-CoV-2 [ 17–19 ]. We developed neutralization assays to investigate protective antibodies against the live SARS-CoV-2 virus in HCW, which most studies have not reported [ 3–11 , 13 , 20–22 , 26 , 32–41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although we demonstrated high SARS-CoV-2 neutralizing antibody titers at three weeks post vaccination, we did not perform experiments to examine the durability of these titers over longer timeframes. Finally, while the presence of neutralizing titers against SARS-CoV-2 is correlated with protection against infection in animal models [48,49] and preliminarily in human studies [50], we did not directly test if the neutralizing antibodies elicited by ΔNA(RBD)-Flu are protective against viral challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We focused our studies on the viral spike protein because it is the main target of neutralizing antibodies (Tortorici and Veesler, 2019), and because anti-spike antibodies are the immune parameter best established to associate with protection against coronavirus infection in humans (Addetia et al, 2020;Callow, 1985;Callow et al, 1990;Lumley et al, 2020;Polack et al, 2020).…”
Section: Phylogenetic Analysis Of 229e Spikes To Identify Historicalmentioning
confidence: 99%